2020
DOI: 10.1002/suco.201900311
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of corroded RC beams: Extending fib Model Code 2010 models

Abstract: The residual resistance of corroded reinforced concrete members depends on steel and concrete cross section loss and deterioration of material properties for steel, concrete, and bond. The paper considers these phenomena in models for resistance calculations, starting from the cross section and stress field models in Model Code 2010. The aim of this study is to develop models proposed by Coronelli et al., using a recently proposed approach by Blomfors et al. to model bond of corroded reinforcement based on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 31 publications
(107 reference statements)
0
11
0
Order By: Relevance
“…The reason may be that for the corroded beams with same load level applied, the corrosion level of steel bars tends to increase with aggregate replacement ratio (see Table 3), while Fernandez et al, 31 and Yang et al 32,33 found that the bond strength between steel bars and surrounding recycled aggregate concrete decreased with the increasing corrosion level of steel bars. Coronelli, 34 Coronelli et al, 35 Blomfors et al, 36 and Zandi et al 37 pointed out that corrosion physically reduced the cross‐section of the transverse and longitudinal reinforcement, cracked the concrete cover and affected the bond strength between the reinforcement and concrete. When the load level is small (not greater than 0.2), with the increase of aggregate replacement ratio, the decreased number of bending cracks due to the degradation of bond performance between steel bars and surrounding concrete is less than the increased number of bending cracks due to the aggregate replacement ratio increases.…”
Section: Resultsmentioning
confidence: 99%
“…The reason may be that for the corroded beams with same load level applied, the corrosion level of steel bars tends to increase with aggregate replacement ratio (see Table 3), while Fernandez et al, 31 and Yang et al 32,33 found that the bond strength between steel bars and surrounding recycled aggregate concrete decreased with the increasing corrosion level of steel bars. Coronelli, 34 Coronelli et al, 35 Blomfors et al, 36 and Zandi et al 37 pointed out that corrosion physically reduced the cross‐section of the transverse and longitudinal reinforcement, cracked the concrete cover and affected the bond strength between the reinforcement and concrete. When the load level is small (not greater than 0.2), with the increase of aggregate replacement ratio, the decreased number of bending cracks due to the degradation of bond performance between steel bars and surrounding concrete is less than the increased number of bending cracks due to the aggregate replacement ratio increases.…”
Section: Resultsmentioning
confidence: 99%
“…strength of corroded RC members 3 and validated them against experimental data. However, for the practical applications of assessment of existing RC structures, important issues need to be addressed.…”
Section: The Demsa Protocol For Rc Structuresmentioning
confidence: 93%
“…Many researchers studied behavior of ordinary RC beams 13–16 on the contrary, the studied of the stepped beams are very rare. The SBs are necessary members, in case of the floors with different levels in one span.…”
Section: Research Significancementioning
confidence: 99%